Intragenic suppressors of induction-deficient tetR mutants: Localization and potential mechanism of action - Biburger, Markus; Berens, Christian; Lederer, Thomas; Krec, Traudl; Hillen, Wolfgang (Journal of Bacteriology, 1998)
Eight Tn10 Tet repressor mutants with an induction-deficient phenotype and with primary mutations located at or close to the dimer interface were mutagenized and screened for inducibility in the presence of tetracycline. The second-site suppressors with wild-type-like operator binding activity that were obtained act, except for one, at a distance, suggesting that they contribute to conformational changes in the Tet repressor. Many of these long-range suppressors occur along the dimer interface, indicating that interactions between the monomers play an important role in Tet repressor induction.
Keywords: Tet repressor; structure-function relationship; DNA binding; Tetracycline